Preparation, Characterization, and Anti-Cancer Activity of Nanostructured Lipid Carriers Containing Imatinib - Hafiz A. Makeen; Syam Mohan; Mohamed Ahmed Al-Kasim; Muhammad Hadi Sultan; Ahmed A. Albarraq; Rayan A. Ahmed; Hassan A. Alhazmi; M. Intakhab Alam (MDPI AG, 2021)
Breast cancer is the most widespread malignancy in women worldwide. Nanostructured lipid carriers (NLCs) have proven effective in the treatment of cancer. NLCs loaded with imatinib (IMA) (NANIMA) were prepared and evaluated for their in vitro efficacy in MCF-7 breast cancer cells. The hot homogenization method was used for the preparation of NANIMAs. An aqueous solution of surfactants (hot) was mixed with a molten mixture of stearic acid and sesame oil (hot) under homogenization. The prepared NANIMAs were characterized and evaluated for size, polydispersity index, zeta potential, encapsulation efficiency, release studies, stability studies, and MTT assay (cytotoxicity studies). The optimized NANIMAs revealed a particle size of 104.63 ± 9.55 d.nm, PdI of 0.227 ± 0.06, and EE of 99.79 ± 0.03. All of the NANIMAs revealed slow and sustained release behavior. The surfactants used in the preparation of the NANIMAs exhibited their effects on particle size, zeta potential, encapsulation efficiency, stability studies, and release studies. The cytotoxicity studies unveiled an 8.75 times increase in cytotoxicity for the optimized NANIMAs (IC50 = 6 µM) when compared to IMA alone (IC50 = 52.5 µM) on MCF-7 breast cancer cells. In the future, NLCs containing IMA will possibly be employed to cure breast cancer. A small amount of IMA loaded into the NLCs will be better than IMA alone for the treatment of breast cancer. Moreover, patients will likely exhibit less adverse effects than in the case of IMA alone. Consequently, NANIMAs could prove to be useful for effective breast cancer treatment.